Situational Leadership of School Principals: Strategies for Strengthening the Quality of Learning in Elementary Schools - Lismeni, Cut Lismeni; Usman, Nasir; Rasyid, Suparta; Ismi Afaidi, Markas (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aimed to analyze the application of situational leadership of elementary school principals in the archipelago to strengthen teacher professionalism and improve the quality of learning. This study focuses on the three main dimensions of situational leadership, namely diagnostic, adaptive, and professional strengthening, as reflective leadership models relevant to the context of education with limited resources. Method: This study used a descriptive qualitative approach involving three elementary schools in Simeulue Regency, Aceh Province, Indonesia. Data were collected through semi-structured interviews, participatory observations, and documentation studies, and then analyzed using the Miles, Huberman, and Saldaña interactive model, which included data reduction, data presentation, and conclusion drawing. The validity of the data was strengthened through the triangulation of sources and methods. Results: The results of the study show that school principals have diagnostic skills in recognizing teacher readiness through reflective, supervision, and open communication. The adaptive dimension is reflected in the principal’s flexibility in adjusting the leadership style from directing to delegating based on the teacher's level of competence. The dimension of professional strengthening can be seen through the role of school principals as mentors, facilitators, and motivators who foster collaboration and appreciation of teacher innovation. These three dimensions form a reflective leadership cycle that encourages the creation of a collaborative learning environment responsive to the context of island schools. Novelty: This model highlights that leadership effectiveness relies not only on the appropriateness of leadership style, but also on teachers’ contextual sensitivity, empathy, and sustained professional growth, forming a holistic and human-centered approach to educational leadership.